Arranjo físico: um estudo do processo de produção de vinho de açaí como proposta de melhoria no leiaute produtivo - MORAES, Daniel Rego (2022)
The current competitiveness and the need for survival in the market, direct companies for the use of techniques that assist in the management and optimization of processes and resources; Therefore, companies need to work on continuous improvement of processes and products in order to reduce costs and maximize the final results. In this sense, the aim of this paper is to present a proposal to review the mapping of the productive process toward optimizing the production process, creating a new layout for the process, through a case study, descriptive, exploratory qualitative character in a vitaminosa located in the Lower Tocantins, in the city of Abaetetuba - PA. This work is divided into two parts. At first, a literature search is done with a survey of the history and characteristics of acai; concepts of the four models of management of the production process, tools used in Lean manufacturing and production process description of the acai berry. In the second, we analyze the value stream and study the layout vitaminosa. It can be argued that one stream mapping appropriate value and studied paying attention to the tools presented by Toyota production system generate significant gains in both cost reduction and increase in productivity.